2022
DOI: 10.1101/2022.07.21.500924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PTPN22 R620W Gene Editing in T Cells Enhances Low Avidity TCR Responses

Abstract: A genetic variant in the gene PTPN22 (R620W, rs2476601) is strongly associated with increased risk for multiple autoimmune diseases and has been linked to altered TCR regulation. Here, we utilize Crispr/Cas9 gene editing with donor DNA repair templates in human cord blood-derived, naive T cells to generate PTPN22 risk edited, non-risk edited (silent modification), or knock out T cells from the same donor. PTPN22 risk edited cells exhibited increased activation marker expression following non-specific TCR engag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The non‐synonymous SNP in PTPN22 (rs2476601) was reported that contributing to influence the signal transduction of TCR in cohort of Type 1 Diabetes (T1D) 38 . And PTPN22 (R620W, rs2476601) increased the activation of TCR and mediated the transduction of the pro‐inflammation phenotype of CD4 + T cells in autoimmune diseases 39 . Genetic variants in PTPN22 may result in the changes of TCR signals and the generation of Tregs, which is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non‐synonymous SNP in PTPN22 (rs2476601) was reported that contributing to influence the signal transduction of TCR in cohort of Type 1 Diabetes (T1D) 38 . And PTPN22 (R620W, rs2476601) increased the activation of TCR and mediated the transduction of the pro‐inflammation phenotype of CD4 + T cells in autoimmune diseases 39 . Genetic variants in PTPN22 may result in the changes of TCR signals and the generation of Tregs, which is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…38 And PTPN22 (R620W, rs2476601) increased the activation of TCR and mediated the transduction of the pro-inflammation phenotype of CD4 + T cells in autoimmune diseases. 39 Genetic variants in PTPN22 may result in the changes of TCR signals and the generation of Tregs, which is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Common allelic variations in CTLA-4 expression levels are major determinants of susceptibility to autoimmune diseases such as autoimmune thyroid disease and RA [32]. PTPN22 is associated with TCR signaling and participates in regulating CBL function in T cell receptor signaling pathways [35]. Mutations in this gene can alter TCR regulation and T cell activation, closely related to the increased risk of various autoimmune diseases, including RA and GD.…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether these variants in the patients lower the threshold for T cell activation sufficiently to break tolerance of self-reactive T cells, we utilized an experimental system employing a low avidity, self-reactive TCR T1D2 isolated from a patient with type 1 diabetes mellitus (29)(30)(31). The T1D2 TCR recognizes a peptide derived from islet autoantigen islet-specific glucose-6 phosphatase catalytic subunit-related protein (IGRP) in the context of HLA-DRB1*04.…”
Section: Synergistic Function Of the Ikfz1 And Ubr4 Variants In Causi...mentioning
confidence: 99%